Invisible lives: Occupied cities as a blind spot in geopolitical research - Yana Suchikova (Geopolitics under Globalization)
This study examines the complexities of researching Ukraine’s occupied territories, where silence often acts as both a defense mechanism and a barrier to understanding. It addresses the causes of informational isolation, including censorship, fear of repression, and restricted access to independent sources. The paper highlights the methodological and ethical challenges researchers face, particularly in working with sensitive data and engaging with vulnerable populations. The roles of universities, citizen science, media, and NGOs are explored as crucial avenues for gathering fragmented but vital information and fostering a broader understanding of life under occupation. Emphasis is placed on integrating FAIR principles (Findability, Accessibility, Interoperability, Reusability) with CARE principles (Collective Benefit, Authority to Control, Responsibility, Ethics) to ensure data are both responsibly managed and ethically used. Combining analytical rigor with reflective narratives, this study advocates for interdisciplinary approaches and strategic collaborations that transcend academic boundaries. These efforts are vital for post-war recovery, reintegration, and developing socially inclusive and sustainable strategies that address the human realities of occupation.